Poverty Porn dalam Filantropi Digital (Studi Literature pada Konten YouTube Willie Salim) - Tania Selasi Amara Azizah; Hariyadi Hariyadi; Masrukin Masrukin (Yayasan Literasi Sains Indonesia, 2025)
Poverty Porn is a phenomenon where a person exploits the suffering of others in an intimate way to attract sympathy and pity. This phenomenon is often utilized by philanthropists, including YouTuber Willie Salim. Willie Salim is the first Indonesian creator to be included in the lineup of “Top Creators” in 2024. Therefore, this research discusses how the concepts of Poverty Porn and commodification and monetization in digital philanthropy are related and relevant to Willie Salim's YouTube content. This research is a qualitative-descriptive research with a literature study method. The data analysis used in this research is conceptual analysis with a literature study approach. The validation in this research is done by prioritizing scientific sources from indexed journals, academic books, and credible news portals. The results show that there is a connection between the concept of Poverty Porn and commodification and monetization in digital philanthropy. Where philanthropic content utilizes Poverty Porn to be commodified with various dramatic narratives of suffering so as to attract public attention, then increase engagement and ultimately increase revenue through YouTube monetization. The linkage of these concepts is relevant to the content uploaded on Willie Salim's YouTube. He also utilized algorithms by using certain keywords such as